Optical genome mapping uncovers clinically relevant structural variants in congenital heart disease with heterotaxy - Min, Shaojie; Sun, Jingwei; Chen, Weicheng; Feng, Zhiyu; Zhuang, Quannan; Gao, Yuan; Lin, Siyi; Sun, Siyu; Lu, Yuquan; Li, Shuolin; Tian, Xueying; Huang, Guoying; et al. (Frontiers in Genetics, 2025)
IntroductionThe genetic factors underlying congenital heart disease and heterotaxy (CHD/HTX) are complex, including copy number variants, loss-of-function mutations, and missense variants, many of which can be detected by high-throughput sequencing. The screening for chromosomal structural variations (SVs) is another important strategy to understand the genetic etiology of CHD/HTX.MethodsWe employed optical genome mapping (OGM), an innovative technique capable of capturing SVs often missed by traditional cytogenetic methods, to screen for SVs in 12 patients with complex CHD/HTX. Several patients had previously undergone chromosomal microarray analysis (CMA) or whole exome sequencing (WES), but their genetic diagnoses remained inconclusive.ResultsBy integrating data from CMA or WES, we analyzed potentially pathogenic SVs in patients with CHD/HTX. In total, we identified 825 high-confidence SVs, including 609 SVs (73.7%) located in intergenic regions or containing introns, pseudogenes, or RNA genes, while 217 (26.3%) overlapped the coding regions of genes. Analyzed through AnnotSV, DECIPHER and OMIM databases, 7 SVs of interest were identified, including: one previously reported pathogenic SV, three SVs overlapping established CHD/HTX associated genes (NOTCH2, KDM6A and CBL), and three SVs located in SMARCA2 and CEP164, which are proposed as candidate susceptibility genes pending further validation.ConclusionOur findings highlight the utility of OGM in analyzing the genetic etiology of CHD/HTX and contribute to broadening of the complex genetic landscape underlying these diseases.